Comparing the Efficacy and Safety of Levetiracetam Versus Phenytoin for Treating the Acute Phase of Neonatal Seizures - Mohammadi, Mahmoud; kadivar, maliheh; sangsari, razieh; mirnia, kayvan; saeedi, maryam; adhami, pedah (Iranian Journal of Child Neurology, 2023)
Objectives Neonatal seizure is a significant problem in this life course, and its timely and effective treatment is crucial. In this study, we compared the efficacy of levetiracetam versus phenytoin for treating the acute phase of neonatal seizures. Materials & Methods In this single-blind case-control study, 60 consecutive children with neonatal seizures referred to the Children’s medical center in Tehran, Iran, in 2018 were studied. Those neonates who had at least 30 minutes of seizure after Phenobarbital treatment were assigned to receive either phenytoin (20 mg/kg) or levetiracetam (initial dose of 40-60 mg/kg) through block randomization. The efficacy and safety of the two drugs were compared between the groups. Results The response rate was 83.3% and 86.7% in phenytoin and Levetiracetam groups, respectively, which was not significantly different between groups (P=1.000). Adverse effects were nearly similar between groups (6.7% in the phenytoin group and 3.3% in the Levetiracetam group, P=1.000). Conclusion Levetiracetam and phenytoin are both practical and safe for treating neonatal seizures.